Fundamentals of digital imaging in medicine - Bourne, Roger (Springer, 2010)
Fundamentals of Digital Imaging in Medicine is a primer for students of medical radiology, designed to demystify the mathematics that imaging theory resides in. The focus on medical imaging accompanied by an approach that forgoes complex mathematics for intuitive explanation makes this book accessible and relevant to the medical radiology student without advanced training in mathematics. Addressing concepts such as spatial frequency and Fourier transformations, the reader is armed with a new understanding and grasp of digital imaging with which to manipulate images to optimize their interpretation. Including over 150 figures to illustrate the fundamental concepts of digital imaging and laid out for easy targeting of the desired information, this book is a must-have for any student of medical radiology who wishes to penetrate the world of medical imaging theory.